Association Between Air Pollution in Lima and the High Incidence of COVID-19: Findings from a Post Hoc Analysis - Vasquez-Apestegui, Vanessa (2020)
Until June 12, 2020, there were 6,308 deaths and 220,749 SARS-CoV-2 positive cases in Peru. In Lima, the total number of COVID-19 deaths in all metropolitan areas was 2,382. The case-fatality rate at the national level was 2.58% and 1.93% in Lima. Higher PM2.5 levels are associated with higher number of cases and deaths of COVID-19. The case-fatality rate (Deaths/cases*100) did not increase with the increase in PM2.5 levels. A higher number of food markets was associated with higher incidence and mortality of COVID-19 (p < 0.01 for both); these associations persisted when cases (r = 0.49; p < 0.01) and deaths (r = 0.58; p < 0.01) were adjusted by the population density. The association of PM2.5 with cases of COVID-19 was maintained after controlling analysis by age, sex and number of food markers.